Food packaging business models as drivers for sustainability in the food packaging industry - Pavón Losada, Juan Antonio; Ferrando, Maite; Moncada, Valeria; Operato, Luigi; Gomes, Leonardo; Rosenow, Phil; Hamd, Wael (Frontiers in Sustainable Food Systems, 2025)
The global food packaging industry faces severe environmental challenges due to its reliance on plastics and the growing demand for convenience. In Europe, food packaging alone accounts for 40.5% of all plastic production, yet only 35% of this waste is recycled. The purpose of this study is to examine business models, technological innovations (like AI, IoT, and blockchain) and the relation with customers to support the transition to a circular economy in food packaging. The research focuses on models such as Safe and Sustainable by Design (SSbD) and reusable and returnable packaging systems, evaluating their potential to minimize environmental impact. A key aspect of the investigation is consumer behavior. While consumers express a preference for sustainable options, actual purchasing decisions often prioritize cost and convenience. The study explores how emerging technologies are transforming packaging design by enhancing product safety and improving supply chain transparency. Additionally, regulatory frameworks, particularly within the European Union, such as the Single-Use Plastics Directive (SUPD) and the Circular Economy Action Plan (CEAP), are driving industry-wide changes toward sustainability. However, disparities in adoption and regulatory compliance on a global scale present significant challenges to implementation. The outcome of this study is a set of strategic recommendations aimed at policymakers, industry leaders, and researchers. These recommendations emphasize the importance of harmonizing global regulations to support sustainable packaging practices, increasing investment in innovation and infrastructure, and balancing the relation between industry and consumers to bridge the gap between intention or preferences and action or behavior.